Entre mers-Outre-mer Spaces, Modes and Agents of Indo-Mediterranean Connectivity - Jaspert, Nikolas (Heidelberg University Publishing (heiUP), 2018)
The history of individual seascapes has recently become a vibrant and innovative field of research. Nonetheless, connections between seas (entre mers) and the imagination of lands "beyond the Sea" (Outre-mer) have only rarely been focused in these contexts. This is precisely the main aim of the present collection of essays, which results from a conference held at Heidelberg University. The individual papers treat various aspects of transmarine connections, their regulation and mental expansion in an Indo-Mediterranean context, which comprises the Mediterranean, the Indian Ocean, as well as projections of seaways to India on other maritime areas, thus spanning a wide chronological spectrum from Egyptian antiquity to the onset of the Atlantic Age in the sixteenth century.